Saving Bravo : the greatest rescue mission in Navy SEAL history - Talty, Stephan (Houghton Mifflin Harcourt, 2018)
"The untold story of the most important rescue mission not just of the Vietnam War, but the entire Cold War: one American aviator, who knew our most important secrets, crashed behind enemy lines and was sought by the entire North Vietnamese and Russian military machines. One Navy SEAL and his Vietnamese partner had to sneak past them all to save him"--